Evaluation of a protocol for selective empiric treatment of fever without localising signs. Issue 2 (1st February 1997) - Browne, G J; Ryan, J M; McIntyre, P
Abstract : A protocol for management of young febrile children at risk for bacteraemia has been used at Westmead Hospital, a university based hospital in the western Sydney region, since early 1994. Implementation of the protocol was retrospectively evaluated for the 12 month period 1 June 1994 to 31 May 1995, using the emergency department log book as the primary data source. Altogether 498 children, aged from 3 months to 3 years, with a fever ⩾39.5 0 C were identified over this period, of whom 291 were admitted to hospital because of evidence of sepsis or identified focal infection and 207 children without focal infection were observed in the short stay annexe of the emergency department. Fifty children, considered at high risk of bacteraemia because of a total white cell count ⩾20 × 10 9  / l received empiric antibiotic treatment with ceftriaxone, of whom 19 subsequently had proved bacteraemia and another 10 had focal infection identified during observation in the short stay annexe. Bacteraemia was due to Streptococcus pneumoniae in 16 cases and Haemophilus influenzae type b in three. No adverse events occurred at follow up.  Use of a management protocol and selection on higher white cell count criterion than previously recommended by US centres resulted in restriction of empiric antibiotic treatment to a small proportion of young febrile children presenting to a busy emergency department of whom 38% were bacteraemic.